The Profile of Research on Exporter–Importer Relationships: A Chronological Analysis. Issue 3 (27th May 2019) - Aykol, Bilge
ABSTRACT: This article presents a chronological analysis of bibliographic and thematic aspects of exporter–importer business relationships research based on a systematic review of 211 articles published between the years 1975 and 2017 in business journals. The study findings indicate that, in terms of bibliographic aspects, this literature is characterized by (a) an increasing collaboration among different institutions and countries, despite a heavy concentration of authors from Europe and North America; (b) a predominance of a small number of scholars producing a substantial part of the literature; and (c) dominance of empirical articles with relatively moderate average impact. In terms of thematic aspects, behavioral dimensions and relationship characteristics constitute the nucleus of the literature, with research efforts focusing on their environmental and internal drivers and performance outcomes. These study findings carry significant implications for major stakeholders of the exporter–importer relationships research, including authors, editors, and conference organizers.